2018
DOI: 10.1007/s00420-018-1308-5
|View full text |Cite
|
Sign up to set email alerts
|

Person-related factors associated with work participation in employees with health problems: a systematic review

Abstract: PurposeThe objective of this systematic review was to explore and provide systematically assessed information about the association between person-related factors and work participation of people with health problems. The research question was: what is the association between selected person-related factors and work participation of workers with health problems?MethodsA systematic review was carried out in PubMed and PsycINFO to search for original papers published between January 2007 and February 2017. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 137 publications
6
42
2
Order By: Relevance
“…Various models describe self-control as decision making related to sacrificing short-term outcomes in favor of longterm interests, which is in accordance with sacrificing social activities, leisure time or career promotions to achieve sustainable employment (de Ridder et al, 2012). This qualitative synthesis has also indicated the relevance of personal values in decision making, which is in line with the review by de Wit et al, who pointed out the importance of personal factors in work participation (de Wit, Wind, Hulshof, & Frings-Dresen, 2018). Balancing both work and a personal life is a challenge for most workers; an imbalance can result in negative health effect such as stress and burnout.…”
Section: Discussionsupporting
confidence: 83%
“…Various models describe self-control as decision making related to sacrificing short-term outcomes in favor of longterm interests, which is in accordance with sacrificing social activities, leisure time or career promotions to achieve sustainable employment (de Ridder et al, 2012). This qualitative synthesis has also indicated the relevance of personal values in decision making, which is in line with the review by de Wit et al, who pointed out the importance of personal factors in work participation (de Wit, Wind, Hulshof, & Frings-Dresen, 2018). Balancing both work and a personal life is a challenge for most workers; an imbalance can result in negative health effect such as stress and burnout.…”
Section: Discussionsupporting
confidence: 83%
“…Authors of a recent review about person-related factors associated with SA found that experienced work-relatedness was associated with SA in some studies whereas an association was absent in other studies ( 13 ). We found no association between experienced work-relatedness and SA, but our data corroborate the importance of chronic illness, prior SA, perceived work ability and age as determinants of SA ( 2–4 , 9–14 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent French primary care based study found a prevalence of work-related common mental health problems among working-age patients of 26% and a systematic review reported similar numbers [ 3 , 15 ]. Insight into patients’ perception of their problem as work-related is essential for GPs, because there is much evidence for a positive relation between problems with returning to work and the cognition of the work-relatedness of the problem [ 28 ]. This is the more relevant in the light of our finding that Dutch patients want their GP to play an active role in WRPs.…”
Section: Discussionmentioning
confidence: 99%